Re-imagining the city : art, globalization and urban spaces - Ball, Bethan; Grierson, Elizabeth; Sharp, Kristen; Thomas, Ellen (Intellect, 2013)
Re-Imagining the City' examines how contemporary processes of globalization are transforming cultural experience and production in urban spaces. It maps how cultural productions in art, architecture, and communications media are contributing to the re-imagining of place and identity through events, artifacts, and attitudes. This book recasts how we understand cities--how knowledge can be formed, framed, and transferred through cultural production and how that knowledge is mediated through the construction of aesthetic meaning and value.